Effect of Antioxidants on the Occurrence of Pre-eclampsia in Women at Increased Risk - Sultan, Mahmoud; Salim, Hassan; El Maslawy, Yahya; Al-Tamimi, Ibrahim; Arafa, Ibrahim (Arab Journal for Sciences and Research Publishing, 2015)
The objective of this work is: Asses the potential benefit of antioxidant supplementation on the occurrence of preeclampsia at high risk women. Patients and Methods: The number of primigravida women’s collected was "294" with gestational age ranged from 18-22 wks. .from (294) prim gravida cases ,(25) women were identified as being at increased risk of pre-eclampsia by abnormal Doppler wave form in either uterine artery at 18-22 weeks’ gestation ( defined as a resistance index < 95th centile for gestation or the presence of an early diastolic notch ) , Another (25) women with history in the preceding pregnancy of pre-eclampsia, eclampsia or HELLP (Hemolysis, elevated liver enzymes, low platelets ) . -Total number of eligible participants were, (50) cases. Design and procedure: Cases divided randomly into two groups each 25 cases one group received tablets of 1000 mg vitamin C, (Cevitil efferecent. EPICO) + 400 iu of vitamin E (E-Viton 400 pharco). Venous blood for measurement of PAI-1 and PAI-2, the primary outcome measure was the ratio PAI-1 / PAI-2 and the secondary outcome prospectively according to guidelines of international society for the study of hypertension in pregnancy. Results: Doppler screening was done on, 294 prim gravidae with gestational age ranged from 18-22 weeks; only 42 women showed abnormal Doppler study so asked to come for rescanning at 24 weeks’ gestation. 31 out of 42 patients (75%) have persistent abnormal study. The remainders of the 42 women (25%) were withdrawn from the study at 24 wks.’ gestation because they have normal uterine-artery scan. Development of mild preeclampsia was statistically lower (p<0.5) in the study than that in the control group. However, development of sever preeclampsia or superimposed preeclampsia was statistically insignificant between both groups. PAI-1 was significantly increased in women developed preeclampsia more than normotensive (167±71.2, 113.8±35.6ng/ml respectively) with P=0.03 IN contrast PAI-2 was significantly decreased in women developed preeclampsia less than normotensive (105±34.9, 181.1±67.9ng/ml respectively) with P=0.018. Conclusion: Treatment and prevention trials of preeclampsia have been disappointing to date. However, this study has suggested causal links between oxidative stress and The development of preeclampsia indicate that it may be a role for antioxidant vitamins in the prevention of preeclampsia. a high- risk population can be successfully identified on the basis of uterine-artery Doppler screening and pervious history of the disease.